Entwined - Dixon, Heather (Greenwillow Books, 2011)
Confined to their dreary castle while mourning their mother's death, Princess Azalea and her eleven sisters join The Keeper, who is trapped in a magic passageway, in a nightly dance that soon becomes nightmarish.